1986
DOI: 10.1161/01.str.17.6.1156
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow changes associated with ethanol intoxication.

Abstract: SEVERAL INVESTIGATORS have reported an association between alcohol abuse and cerebrovascular disease.1 "* Neuropsychiatric complications of chronic, excessive consumption of ethyl alcohol are often associated with significant reductions in cerebral blood flow (CBF).9 -" Reduction in cerebral blood flow is seen following acute ethanol withdrawal with normalization in a few days. 12Studies on the acute effect of ethanol on CBF have produced conflicting results. Most animal studies indicate a vasoconstrictive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Investigators have found decreased rCBF in cerebellum and increased rCBF in the parietal and prefrontal cortex (Volkow et al, 1990), increased rCBF in the frontal cortex only (Matthew and Wilson, 1986), increased rCBF in the right prefrontal cortex (Tiihonen et al, 1994), and increased rCBF in all gray matter areas except the left anterior cortical areas (Newlin et al, 1982). Decreased CMRglu was found in frontal cortices (De Wit et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have found decreased rCBF in cerebellum and increased rCBF in the parietal and prefrontal cortex (Volkow et al, 1990), increased rCBF in the frontal cortex only (Matthew and Wilson, 1986), increased rCBF in the right prefrontal cortex (Tiihonen et al, 1994), and increased rCBF in all gray matter areas except the left anterior cortical areas (Newlin et al, 1982). Decreased CMRglu was found in frontal cortices (De Wit et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations of normal, healthy subjects have revealed that moderate ethanol inebriation is followed by a global increase in cerebral blood flow (CBF) during rest (Mathew & Wilson, 1986;Newlin, Golden, Quaife, & Graber, 1982;Sano et al, 1993). Most likely this is caused by a global vasodilatatory effect of ethanol (Greenberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of low doses of alcohol to human subjects, doses that produce mild levels of intoxication (0.5-1.0 g/kg), increased cerebral blood flow in specific regions. 12,13,[36][37][38][39] The prefrontal and temporal cortices were frequently activated in this low dose range. 12,13,83 The frontal cortex appears to be most sensitive.…”
Section: Dose Dependencymentioning
confidence: 87%